Detection of Malassezia spp. from healthy cattle and cattle with otitis by direct xamination and culture - Duarte, Eduardo Robson; Hahn, Rosane Christine; Hamdan, Júnia Soares (Acta Scientiae Veterinariae, 2018)
The occurrence of bovine external otitis in tropical regions is predominantly assigned to parasitic infestations . These infections represent a significant problem and can be associated with vestibular disease and death. Yeasts of the genus Malassezia are members of the normal microbiota on human and animal skin, and may also be associated with bovine parasitic otitis. The purpose of this study was to evaluate the prevalence of the genus Malassezia in healthy cattle and cattle with otitis by direct microscopic examination and culture. Specimens of 1010 cattle were collected with sterile swabs, inoculated onto Mycosel medium, supplemented with olive oil, and incubated at 32oC for one week. In addition, 200 cattle (143 healthy and 57 with otitis) were also evaluated by direct microscopic examination using a Gram staining method to detect Malassezia spp.. Using the direct examination of the specimens no significant difference was observed between the presence of Malassezia spp. from 143 healthy animals (30.7%) and from 57 animals with otitis (26.3%). Culture was positive for Malassezia spp. in 329 (38.12%) of a total of 863 healthy cattle and in 93 (63.27%) of 147 cattle with otitis (p<0.001). In this study the detection of Malassezia spp. from cattle with a high level of confidence was possible by culture. This exam was much more specific, allowing a much more accurate visualisation of yeast cells and giving isolates for biochemical tests.